2006
DOI: 10.1016/j.ijsolstr.2006.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Variational analysis of transverse cracking and local delamination in [θm/90n]s laminates

Abstract: A displacement-based variational model is developed to study the effects of transverse cracking and local delaminations in symmetric composite laminates. In the model, the crack shape is assumed to be a function of crack density and delamination length. Using a variational approach with the principle of minimum potential energy, governing equations are derived. The effective Young's modulus E x and energy release rate G are theoretically examined as a result of local delaminations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Numerical results have shown that stiffness reduction of the 90 ply strongly depends upon the orientation of the adjacent ply group, with the remote constraining layer having negligible influence. Zhang and Minnetyan (2006) developed a displacement-based variational model to study the effect of transverse cracking and local delamination in symmetric composite laminates, assuming the crack shape to be a function of crack density and delamination length. Using a variational approach, they examined the effect of delamination on the effective Young's modulus of the laminate and the strain energy release rate.…”
Section: Residual Stiffness Of Composite Laminate With Crack-induced mentioning
confidence: 99%
“…Numerical results have shown that stiffness reduction of the 90 ply strongly depends upon the orientation of the adjacent ply group, with the remote constraining layer having negligible influence. Zhang and Minnetyan (2006) developed a displacement-based variational model to study the effect of transverse cracking and local delamination in symmetric composite laminates, assuming the crack shape to be a function of crack density and delamination length. Using a variational approach, they examined the effect of delamination on the effective Young's modulus of the laminate and the strain energy release rate.…”
Section: Residual Stiffness Of Composite Laminate With Crack-induced mentioning
confidence: 99%
“…Considering an interface j (in this case, a 3D matrix layer of thickness H e 20 , where H e is the thickness of the elementary ply) between two cracked plies S i and S i+1 , the upper part S + and the lower part S − of the laminate are homogenized. Periodic boundary conditions are defined.…”
Section: The Bridge Between Micromechanics and Mesomechanicsmentioning
confidence: 99%
“…The description of the interaction between delamination and transverse microcracking is a rather ancient question in micromechanics [13][14][15][16][17][18][19][20][21][22]. In all the referred works, two-dimensional discrete models are used.…”
Section: Introductionmentioning
confidence: 99%
“…This damage phenomena has been widely addressed by micro-mechanical approaches in the literature; mostly by analytical methods [1][2] and especially by shear-lag method [3][4][5][6] . Variational technique [7][8][9] and finite element methods [10][11] have been generally used for deriving the stress distribution at the 90˚/0˚ interface. Each method contains specific assumptions and outcome with considerable progress in the field 12 .…”
Section: ) Introductionmentioning
confidence: 99%